Experimental design and molecular dynamics in herbal plant processing: A reviews - N. A., Hashim; Siti Kholijah, Abdul Mudalip; Noorlisa, Harun; Rohaida, Che Man; Siti Zubaidah, Sulaiman; Zatul Iffah, Mohd Arshad; Shalyda, Md Shaarani (2018)
Herbal plant currently has become significant and widely known due to its extensive sources of therapeutic phytochemicals agents. The practice of herbal plant as remedy has been adapted since thousands of years by ancient civilization such China, Mesopotamia, Egypt and India [1]. Unlike the modern drugs, treatment with herbal plant possess a range of therapeutic value and considered as safe since there is no or minimal side effect [2]. Previous study had proven that herbal plant able to treat ailment such as fever, antihypersensitive, diabetes, diarrhoea and even cancer [3]. Based on present-day scenario, the used of herbal plant as a therapeutic agent had increased mainly due to growing recognition and claim that herbal based product are safe, effective, non-toxic and minimal side effect as these remedies are in sync with nature. On the other side, the implementation of herbal plant in treating ailment seems to be a promising alternative for entire community as it is easily available, afforadable and also cultural acceptability. Recently, World Health Organisation (WHO) estimated that more that 80% of the world population rely on herbal medicine for some part of their healthcare [2]. As for that, emerging for continous research and development for herbal plant is crucial as the demand increases throughout the year.